Цукровий діабет 2-го типу: шляхи профілактики, запобігання розвитку - Кравчун, Н. О.; Козаков, О. В.; Романова, І. П.; Земляніцина, О. В. (Clinical Endocrinology and Endocrine Surgery, 2011)
The existing principal approaches to development of national screening programmes in various countries and Ukraine were given and analyzed in the review. The urgency of the problem was proved. It was pointed that detection and control of risk factors was the obligatory part of the type II diabetes mellitus screening.